Kemampuan Motorik Halus Anak Usia Dini di TK Khasanah Islamic Entrepreneur Preschool - Dahlia Dahlia (Jurnal Hikmatuna, 2015)
The frequent use of media crayons in coloring activities cause boredom in this activity, so we need a new media that can make children interested in doing the coloring activity. This is the reason the author in formulating the research problem, namely how the coloring activity can improve fine motor skills children in group A2 Kindergarten Khasanah Islamic Entrepreneur Preschool. This study used a qualitative descriptive approach. Collection techniques data used in this study is the observation, documentation, and administration tasks. Data were analyzed using qualitative and quantitative approaches, namely data obtained is converted into a percentage. The subjects were a group A2 Kindergarten Khasanah Islamic Entrepreneur Preschool, amounting to 5 boys. Selection of the subject of research carried out in class because the fine motor skills a child does not develop optimally so that children have difficulty writing.Based on the above results, the authors conclude that the coloring activity with the media food coloring can improve fine motor skills children in of group A2 kindergarten Khasanah Islamic Entrepreneur Preschool. An increase can be seen before and after carrying out the coloring activity with food coloring media. Using food coloring media, fine motor skills children increased by25%.